Assessment of an Aujeszky's Disease Control Strategy in a Highly Prevalent Pig Farm Based on Systematic Vaccination With an Inactivated gE-Negative Marker Vaccine - Aznar, María N.; Bessone, Fernando A.; Segurado, Rodrigo; Duffy, Sergio J. (Frontiers in Veterinary Science, 2022)
Aujeszky's disease (AD) is endemic in Argentina. In 2016, an inactivated gE- negative marker Bartha K61 vaccine (AUSKIPRA® BK) was launched for use, making Argentina the only country to carry out a control strategy plan with it. In the present article, we describe the results of a control program in a farrow-to-finishing farm with high initial AD prevalence (33% in sows), based on the systematic vaccination, detection, and elimination of seropositive pigs, the replacement of sows with vaccinated gilts, and the instauration of artificial insemination. The program was suitable for diminishing the incidence and the prevalence at levels consistent with virus eradication. This situation has been sustained over time. This is the first report of AUSKIPRA® BK efficacy under field conditions.